2018
DOI: 10.1177/1356766718771420
|View full text |Cite
|
Sign up to set email alerts
|

Influence of users’ psychosocial traits on Facebook travel–related behavior patterns

Abstract: The principal aim of the article was to explore the psychological aspects of Facebook (FB) users’ travel-related behavior on FB. This especially refers to the time they post their travel-related information, the type of information they post (photos, videos, comments, etc.), when they watch the photos of other people, are they keen to post the information when their impressions are positive or negative, and what level of privacy they keep (with whom they are sharing travel-related information). A total of 804 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The theme of staff is mainly used in positive tones in the reviews shared by passengers. This finding is concordant with the research done by Brochado et al [2] and Ban and Kim [53]. In parallel with our findings, research done by Sezgen et al [3] also found that the theme of staff was one of the most dominant themes that appeared in the review of passengers, while the staff was the most common factor driving satisfaction for all passenger groups, in line with our finding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The theme of staff is mainly used in positive tones in the reviews shared by passengers. This finding is concordant with the research done by Brochado et al [2] and Ban and Kim [53]. In parallel with our findings, research done by Sezgen et al [3] also found that the theme of staff was one of the most dominant themes that appeared in the review of passengers, while the staff was the most common factor driving satisfaction for all passenger groups, in line with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…Few numbers of studies are increasingly realizing that the airline passengers' online commentaries represent a rich vein of data for contributing to the analysis of passengers' experiences. Recent literature has identified both the influence of online user-generated content [53] and the valuable research possibilities inherent in examining them [2]. The present study follows this emerging style of work and redeploys the rich commentary data available on a major international review site, TripAdvisor, especially in the time of COVID-19.…”
Section: User Generated Content In Airlines Researchmentioning
confidence: 91%
“…(2) the measurement of engagement with DMOs/NTOs' SNSs [9,21]; (3) the analysis of the drivers of travelers' engagement with and contribution to DMOs/NTOs' SNSs [42,43]; (4) new methodologies to measure travelers' attitudes towards destinations and attractions by means of SNSs' content analysis [20,22,30,44]; (5) tourists' destination experiences with DMOs' SNSs [45][46][47][48][49]; and (6) the impact of DMOs' SNSs on online travelers' attitudes, visit and recommendation intentions, reactions to marketing and advertising messages, and bookings [29,31,33,[50][51][52][53][54][55][56][57][58]. Overall, and regardless of the topic covered, there is a prevalence of studies on Facebook (31 studies), Twitter (21 studies), YouTube (15 studies) and TripAdvisor (10 studies).…”
Section: Level Of Analysismentioning
confidence: 99%
“…The drivers of adoption and acceptance of Web 2.0 technologies by DMOs' SNSs users and travelers have been analyzed in relation to several factors: demographic characteristics of the users/travelers [47,54]; motivation to visit the destination [29]; information sources needed [29]; past experience of destination visitation [33]; psychological, temporal and spatial distance to/from the destination [58]; identity and self-concepts [43,53]; emotions [25]; type of platform adopted [29]; level of interactivity [15,22,53,71]; media exposure [28]; and devices used [49].…”
Section: Drivers Of Adoption and Acceptance Of Web 20 Technologiesmentioning
confidence: 99%
“…Facebook is currently the most widely used and influential social network on the Internet and one of the most popular websites worldwide (Jovanović et al, 2018). On December 31 st 2017, Facebook had reached 2.13 billion monthly active users, nearly half the world's estimated online population (Internetworldstats, 2018).…”
Section: Introductionmentioning
confidence: 99%